REVIEW ARTICLE: Should Patients with Low to Moderate Surgical Risk be Offered TAVI Instead of Conventional Aortic Valve Replacement in the Management of Symptomatic Aortic Stenosis?. (2015) - , Charles Malcolm Rees; Ho, Eric
No abstract available